Sosialisasi I Care Tuberkulosis dengan Gerakan Bersama (Geber) di SMA Negeri 1 Bengkayang - Wahyuni, Tri; Ariyanti, Sri; Hastuti, Lidia; Kardiatun, Tutur; Erlando, Zeri; Hapis, Hapis; Putri, Nur Ahlam Nadia (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2023)
This service aims: to provide socialization and counseling on the prevention of TB disease to increase public awareness about the dangers of TB disease and its prevention. The activity method used in this service is in the form of training/workshop and the results of the training are presented to teachers and students. Through stages 1) lecture 2) simulation 3) exploration 4) mentoring and 5) evaluation. The target audience or participants in the counseling were students of SMA 1 Bengkayang State. The results of the service activities show that the community is very enthusiastic about participating in counseling activities as seen by the very good response. Considering that this activity is very important to increase students' knowledge, this activity can be continued in other lower-class communities so that they can maintain a clean environment so as to avoid infectious diseases such as tuberculosis